"Номовые государства", "территориальные царства", "полисы" и "империи". Проблемы типологии - Дьяконов, И. М.- Якобсон, В. А.
Diakonoff, I. M.-Jakobson, V.A., "Nome States", "Territorial Kingdoms", "Poleis" and "Empires". A Study in Typology; engl. Résumé.